Tolerance and sorption of Bromacil and Paraquat by thermophilic cyanobacteria Leptolyngbya 7M from Costa Rican thermal springs - Brenes Guillén, Laura Natalia (2019)
We studied the adsorption ability and tolerance of the thermophilic filamentous cyanobacteria Letolyngbya 7M towards Paraquat and Bromacil. Adsorption isotherms at pH = 7.0 showed an adsorption capacity of 24.4 mg/g and 66.8 mg/g, respectively, and a good fit to the Langmuir model (R2 = 0.97 and 0.99, respectively). To evaluate the effect of both herbicides on photosynthetic pigments and viability of cyanobacteria, cell autoflorescence and esterase activity was determined using flow cytometry. Autofluorescence was less sensitive to changes in cell viability, as it was only slightly reduced at high Paraquat and Bromacil concentrations. Herbicide effect on esterase activity is dose-dependent. Bromacil did not cause a significant effect on either chlorophyll a content or cell viability. This study demonstrates the potential of Leptolyngbya 7M to remove Paraquat and Bromacil herbicides from aqueous solution under laboratory conditions.